EFFORTS ARE MADE TO INCREASE REVENUE THROUGH E-COMMERCE IN THE FRAMEWORK OF PANDEMIC COVID-19 - Hane Johan; Iljasmadi Iljasmadi; Zuraedah Indah; Budi Harto; Haderah Haderah; Helendra Helendra (Jurnal Abdimas Bina Bangsa, 2022)
Community Service (PKM) is a form of the Tridharma of Higher Education. This PKM is proposed to carry out outreach and educational activities in Nagari Difficult Water Community empowerment is an effort to raise awareness and develop the potential possessed by the community to increase family income. Community participation in development is needed because the community is the subject of development which is responsible for improving their welfare independently. Community participation in development is a concept from the community empowerment paradigm. In its realization, community empowerment mostly focuses on economic empowerment in the context of poverty alleviation or poverty alleviation, especially during the Covid-19 pandemic. Community empowerment is always carried out in the form of developing productive activities to increase income. Community economic empowerment seeks to develop home industry-based Micro, Small and Medium Enterprises (MSMEs) so that they can increase family income during the Covid-19 pandemic